Karakteristik Sosial Ekonomi Nelayan Payang di Pelabuhan Perikanan Nusantara Brondong Lamongan Jawa Timur - Iwan Fadli Pasaribu; Sahat Supripto Imanuel Harianja (Universitas Wijaya Kusuma Surabaya, 2023)
Payang is a bag net fishing gear used to catch schools of fish. Payang fishing gear is one of the most commonly used fishing gears by fishermen in the waters around PPN Brondong, Lamongan regency. This study aims to examine and study the socio-economic characteristics of Payang fishermen. The method used in this research is a descriptive method with purposive sampling technique. The main components of the Payang fishing gear construction are floats, weights, float lines, weight lines, net ropes, wings, body I, body II, and bag. Most of the Payang fishermen's family members are around 4-6 people. The educational level of Payang fishermen is relatively low, with graduates of elementary school and even some who have never been to school. The tradition of sea harvesting is a high social value tradition carried out by Payang fishermen based in PPN Brondong, Lamongan. The economic aspect of fish catching with fishing gear in PPN Brondong consists of fixed costs of IDR 210,994.51 and variable costs of IDR 904,000, making the total cost IDR 1,114,994. The profitability of the fishing business conducted by Payang fishermen based in PPN Brondong is feasible because the RC/ratio value is greater than 1.Keywords : Fisherman, Payang, Revenue